Pengaruh Kualitas Pelayanan Dan Harga Terhadap Loyalitas Pelanggan Angkringan Muhibbin Kemayoranjakarta Pusat - Novita, Salsabil Nabila; Rahmadi, Heksawan; Nurseno, Bertadi (JAMBIS : Jurnal Administrasi Bisnis, 2023)
Angkringan is a concept of food stores operate on the outskirts of roads or sidewalks. The concept of angkringan highlights from business people in Blora to innovate by changing ordinary angkringan on the side of the road becomes like a cafe or a place to eat modern. Modern Angkringan is growing rapidly along withpopularity of culinary tourism. Not only the concept of angkringan changed like the cafe, they even offer live acoustics on certain days. To attract customers from the upper middle class, they promoting cafes with angkringan label. Angkringanhas a menu various simple snacks include various fried foods and satay which also known as sundukan, in addition to providing a variety of warm drinks such as tea, ginger, and coffee. Typical dishes from the angkringan menu famous is ricewrap, or also known as Sego Kucing or Nasi Kucing (because of its small portion), which is served with tempeh Fry and small pieces of Whitefish or anchovies. The purpose of this research is to discover, develop and testsomething true and real opinion on the object under study. Technique data collection using questionnaires. This research uses quantitative methods with independent variables that influence the quality Service and Price and the dependent variable is customer loyalty Warung Angkringan WM Kemayoran. Population in this study as much 130 respondents. Data collection techniques using questionnaires.